ANALISIS MAKNA VISUAL DARI POSTER IKLAN SABUN LIFEBUOY ANTI KUMAN NO 1 DIDUNIA - cici septiasari; Sabri (Jurnal Ilmu Komunikasi Balayudha, 2023)
Advertising posters are a complement to information in which there are short and clear words accompanied by signs, advertising posters with visual and verbal meanings that are created to attract the audience and give an impression to those who see it. To find out the meaning and the signs on the poster, one must study and pay more attention to it. Life buoy soap is a well-known soap for protection from all kinds of bacteria to protect all people. The purpose of this study was to find out the visual meaning, verbal meaning and signs on the advertising poster for life buoy soap "No. 1 Anti-Germic Soap in the World". The method used in this study as a tool to understand research is the semiotic method of Rolan Barthes, a study understand a marker or sign in a visual and verbal meaning accompanied by denotation and connotation. From the research results, the life buoy soap advertisement poster has a visual and verbal meaning that is in accordance with the information and signs listed on the life buoy soap advertisement poster “No.1 Anti-germicidal Soap in the World” Keywords: poster, lifebuoy soap, semiotics, Rolan Barthes